Wages of childhood immigrants in Sweden: Education, returns to education and overeducation - Katarina Katz; Torun Österberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
We analyse full-time monthly wages of employees with parents born in Sweden and of childhood immigrants who arrived before the end of compulsory school-age. We use a detailed disaggregation of background countries, which shows considerable heterogeneity, in overeducation, in returns to education and in birth-country coefficients, unexplained by wage models. Both the non-European childhood immigrants and of those from Southern Europe suffer a wage disadvantage relative to natives, men to a larger extent than women. Returns to education are generally lower for non-European childhood immigrants than for natives. Comparison with workers, who immigrated as adults, shows that the childhood immigrants of most nationalities run lower risk of being overeducated and have a smaller wage disadvantage. The child/adult immigrant difference is larger, the larger the disadvantage of the adult immigrants from a country of origin. But for male childhood immigrants from some of the labour transmitter countries, the risk of overeducation is larger than it is for adult immigrants and the difference in adjusted wages between childhood immigrants and adult immigrants also tends to be smaller than for other countries of origin.
Keywords: J31; J61; J15; I24; 330; wages; immigrants; childhood immigrants; returns to education and over-education; Migranten; Lohnstruktur; Bildungsertrag; Unterbeschäftigung; Schweden